Hiatus hernia and interstitial lung abnormalities. Issue 5 (19th November 2020) - George, Peter M.; Hida, Tomoyuki; Putman, Rachel K.; Hino, Takuya; Desai, Sujal R.; Devaraj, Anand; Kumar, Sacheen; Mackintosh, John A.; Gudnason, Vilmundur; Hatabu, Hiroto; Gudmundsson, Gunnar; Hunninghake, Gary M.
The prevalence of hiatus hernia in patients with idiopathic pulmonary fibrosis (IPF) is ∼40% [1–3], greater than the prevalence of hiatus hernia in other chronic lung diseases. While the role of gastro-oesophageal reflux disease (GORD) and its treatment remain an area of controversy in IPF [4, 5], hiatus hernia is associated with reduced survival [2, 3 ] and more rapid lung function decline [3 ]. The cause for the increased prevalence of hiatus hernia in IPF remains unknown. It is possible that the increased rate of GORD associated with hiatus hernia leads to frequent chronic micro-aspiration events [1 ], which could contribute to the development of pulmonary fibrosis. Alternatively, it is plausible that as IPF progresses, the biomechanics of the fibrotic lung result in progressively more negative intrathoracic pressure causing cranial migration of the oesophagogastric junction (GOJ) and stomach into the thorax. The association between hiatus hernia and early stages of pulmonary fibrosis has not been assessed previously. Hiatus hernia is not associated with ILA or its progression, but is twice as prevalent in those with UIP than other subtypes and those without ILA. Moderate to large hiatus hernia is strongly linked to an increased risk of mortality across 4885 participants https://bit.ly/3gy7yq7